Epidemiology of burns caused by moxibustion in Korea. Issue 7 (November 2016) - Yoon, Cheonjae; Cho, Young Soon; Park, Seungchoon; Chung, Sung Phil; Choi, Young Hwan
Highlights: Moxibustion is a common traditional Oriental treatment for various conditions. The epidemiology of moxibustion induced burn is not well understood. Patients underwent moxibustion in their home or in Oriental medicine clinics. Non-abdominal burn sites were associated with a higher frequency of deep burns. Moxibustion should be performed with care at non-abdominal sites. Abstract: Introduction: Moxibustion, a traditional Chinese treatment that uses dried Artemisia argyi, is a common cause of burns treated in Korean hospitals. We aimed to examine the characteristics of moxibustion-induced burns. Methods: This retrospective study examined the records of 59 patients who were treated for moxibustion-induced burns (April 2014–October 2015). All patients completed a questionnaire regarding their general characteristics and moxibustion use. Results: The patients included 16 men and 43 women (average age: 49.1 years, 68 burn sites). Superficial second-degree burns were present at 21 sites, deep second- or third-degree burns at 44 sites, and unknown burns at 3 sites. The most common sites were the lower extremities, abdomen, and upper extremities. The most common practitioners were the patients (27/59, 45.7%) and Oriental medicine practitioners (23/59, 38.9%). The most common locations were the patient's home, Oriental medicine clinic, and moxibustion clinic. The most common reason for moxibustion was pain. Only the burn site was significantly associated with burn depth, and non-abdominal sites were 9.37-fold more likely to involve deep burns (vs. abdominal sites). Conclusion: Korean patients routinely undergo moxibustion, and care must be taken when using moxibustion at non-abdominal sites, due to the risk of deep burns.